Bacterial Acid Resistance Toward Organic Weak Acid Revealed by RNA-Seq Transcriptomic Analysis in Acetobacter pasteurianus - Yang, Haoran; Yu, Yongjian; Fu, Caixia; Chen, Fusheng (Frontiers in Microbiology, 2019)
Under extreme acidic environment, bacteria exploit several acid resistance (AR) mechanisms for enhancing survival, which is concerned from several aspects, such as issues in health and fermentation for acidic products. Currently, knowledge in bacterial AR mainly comes from the strong acid (such as hydrochloric acid) stresses, whereas AR mechanisms against organic weak acids (such as acetic acid), which are indeed encountered by bacteria, are less understood. Acetic acid bacteria (AAB), with the ability to produce acetic acid up to 20g/100mL, possess outstanding acetic acid tolerance, which is conferred by their unique AR mechanisms, including pyrroloquinoline quinine-dependent alcohol dehydrogenase, acetic acid assimilation and molecular chaperons. The distinguished AR of AAB towards acetic acid may provide a paradigm for researches in bacterial AR against weak organic acids. In order to understand AAB’s AR mechanism more holistically, omics approaches have been employed in the corresponding filed. However, the currently reported transcriptomic study was processed under low-acidity (1g/100mL) environment, which could not reflect the general conditions that AAB face with. This study performed RNA-Seq transcriptomic analysis investigating AR mechanisms in Acetobacter pasteurianus CGMCC 1.41, a widely-used vinegar-brewing AAB strain, at different stages of fermentation, namely, under different acetic acid concentrations (from 0.6 to 6.03 g/100mL). The results demonstrated the even and clustered genomic distribution of up- and down-regulated genes, respectively. Difference in AR between AAB and other microorganisms was supported by the down-regulation of urea degradation and trehalose synthesis related genes in respond to acetic acid. Detailed analysis reflected the role of ethanol respiration as the main energy source and the limited effect of acetic acid assimilation on AR during fermentation, and the competition between ethanol respiratory chain and NADH-, succinate dehydroarenes-based common respiratory chain. Molecular chaperons contribute to AR too, but their regulatory mechanisms require further investigation. Moreover, pathways of glucose catabolism and fatty acid biosynthesis are also related to AR. Finally, 2-methylcitrate cycle was proposed as AR mechanism in AAB for the first time. This study provide new insight into AR mechanisms of AAB, also indicates the existence of numerous undiscovered AR mechanisms.